Hybrid Automatic Control System of the Cascade of Centrifugal Extractors; Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Zelenetskaya E. P. Ekaterina Petrovna (Radiation Technologies in Medicine, 2015)
Title screen